Collaborating Digital Social Media For Teaching Science And Arabic in Higher Education During COVID-19 Pandemic - Abdillah, Leon; Handayani, Trian; Rosalyn, Ellen R; Mukti, Yogi I (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
Globalization does not only involve the spread of massive information technology throughout the world. In the early 2020s the world also experienced a global pandemic COVID-19 which plagues almost all countries in the world. COVID-19 forces learning activities di higher education level to be carried out with social distancing concepts. Online learning can be done using a number of popular information technology applications. The study involved college students from the faculty of computer science and engineering. They took courses on enterprise resource planning, human-computer interaction, and research methods. The results showed that COVID-19 did not impede learning activities. A number of social technologies such as Dropbox, Facebook, Google Forms, Moodle, WhatsApp, WordPress, YouTube, and Zoom have seen a surge in usage to support distance learning activities during the COVID-19 pandemic. With online distance learning mode, all learning activities can be done with the concept of work from home. This learning scheme can be used not only for science and technology fields but also Arabic learning.